Magnetic biochar composite material as well as preparation method and application thereof
By preparing a magnetic biochar composite material with a heterostructure of Fe3O4 nanocrystals and zero-valent iron nanodots, the problems of ash interference, iron phase separation and uncontrollable reduction in existing iron-loaded biochar in soil remediation were solved, achieving efficient degradation of organic pollutants and soil ecological protection.
Patent Information
- Application Number
- CN202511777004.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-28
- Publication Date
- 2026-01-13
AI Technical Summary
Existing iron-loaded biochar preparation technologies suffer from problems such as ash interference, iron phase separation defects, and uncontrollable reduction, resulting in low degradation efficiency of organic pollutants such as antibiotics in soil remediation, secondary pollution caused by reliance on exogenous H2O2 addition, and uncontrolled iron-carbon interactions, making it impossible to construct an effective heterojunction interface.
A magnetic biochar composite material with a heterostructure of Fe3O4 nanocrystals and zero-valent iron nanodots was prepared by pyrolyzing agricultural waste under a protective atmosphere and treating it with inorganic acid to generate a low-ash carrier. A reducing agent was then added in a buffer environment to form a green rust-type precursor. Finally, the composite material was pyrolyzed in a mixed atmosphere of N2 and H2 to prepare the magnetic biochar composite material with a heterostructure of Fe3O4 nanocrystals and zero-valent iron nanodots.
It improves iron loading and dispersibility, enhances catalytic activity, avoids the need for exogenous oxidants, promotes endogenous Fenton-like reactions in the soil, achieves efficient degradation of organic pollutants, reduces remediation costs, and maintains soil ecological health.
Smart Images

Figure CN121314543A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of soil remediation, and particularly relates to a magnetic biochar composite material and a preparation method and application thereof. BACKGROUND
[0002] Organic pollutants can migrate over long distances through different environmental media (such as air, water and organisms, etc.) and persist in the environment. In particular, those difficult-to-degrade organic pollutants (such as antibiotics) have relatively low distribution concentrations, but have long-term residual, high biological accumulation and difficult-to-decompose characteristics in the soil environment, which pose a serious threat to the ecological environment and human health. Therefore, it is urgent to develop a green and efficient technology for promoting the degradation of organic pollutants in soil while maintaining the ecological health of soil.
[0003] Since iron minerals are ubiquitous in natural soil, the catalytic natural Fenton-like oxidation system (Fe(II) / O2) has the potential to be applied to in-situ remediation of antibiotic-contaminated soil. However, the endogenous Fenton-like system in soil has very limited effect on the degradation of pollutants due to slow Fe(III) / Fe(II) cycle and low O2 activation efficiency.
[0004] Efficient iron cycling is the key to effectively remove antibiotics by Fenton-like oxidation technology. Biochar is a highly aromatic and refractory polymer produced by pyrolysis of biomass under limited oxygen conditions, and its unique quinone and aromatic structure endows it with significant redox activity. At the same time, it has the dual role of soil amendment and redox catalyst, and can form a highly active redox microenvironment after being applied to soil, thereby adjusting biogeochemical processes, especially Fe(III) / Fe(II) cycle, through “excitation effect”. In addition, biochar can receive, provide (battery-like effect) and conduct (conductor-like effect) a large number of electrons in environmental media through biological and non-biological pathways. This property enables it to regulate the form, redox state and bioavailability of iron by affecting the electron transfer process, ultimately affecting the generation of reactive oxygen species (ROS). In addition, in the Fenton reaction system, Fe(II) plays a role in exciting and transferring electrons, but the consumption rate of Fe(II) is much greater than its generation rate. In order to ensure efficient degradation of pollutants, it is often necessary to increase the dosage of Fe(II), and thus the carrier iron biochar emerges as the times require. It can further increase the Fe(II) content in soil and increase the oxidation driving force of the Fenton-like reaction system, thereby improving the degradation efficiency of pollutants such as antibiotics.
[0005] However, the existing iron-loaded biochar preparation technology is mainly iron salt impregnation co-pyrolysis method, the core of which is to mix biochar with iron salt directly, and then further pyrolyze in inert atmosphere to realize iron reduction and carrier compounding. However, the following problems are easily caused: (1) Ash interference problem: CaO, MgO and other metal oxides (content > 8 wt%) generated by pyrolysis of agricultural waste (straw / rice husk) form a molten phase wrapping active sites at high temperature, resulting in: iron loading < 5 wt%.
[0006] (2) Iron phase separation defect: iron salt impregnation co-pyrolysis method generates FeO / FeS2 inert impurities due to the interference of biomass components, both of which cause iron particle agglomeration and low dispersion, resulting in low loading efficiency; (3) Uncontrollable reduction drawbacks: imbalance of reducing atmosphere control in the secondary pyrolysis stage, inert atmosphere (N2) only generates pure Fe3O4, and the catalytic activity is limited, and too much H2 content causes Fe3O4 to be completely reduced to micron-sized Fe 0 Agglomerates (particle size > 200 nm), low electron transfer rate.
[0007] The above defects cause the existing materials to have serious limitations in soil remediation: (1) long half-life and low degradation efficiency of organic pollutants such as antibiotics; (2) secondary pollution caused by the addition of exogenous H2O2; (3) although the iron salt impregnation co-pyrolysis method simplifies the process, the iron-carbon interaction is out of control (interference of biomass volatiles and sulfur elements) during pyrolysis, and an effective heterojunction interface cannot be constructed. SUMMARY
[0008] The purpose of the present application is to provide a magnetic biochar composite material and its preparation method and application, which solves the various problems existing in the current biochar material in soil remediation.
[0009] The present application is realized by the following technical solutions: The present application discloses a preparation method of a magnetic biochar composite material, comprising the following steps: Step 1, crushing and drying the agricultural waste, pyrolyzing under a protective atmosphere to 500-700 ℃, obtaining biochar; The biochar is treated with an inorganic acid solution, washed to neutral and dried to obtain a low-ash carrier; Step 2, adding the low-ash carrier to an iron salt impregnation solution, adding a reducing agent solution in a pH 5.5-6.5 buffer environment, and reacting to generate a green rust type precursor; Step 3, pyrolyzing the green rust type precursor in a mixed atmosphere of N2 and H2 to 650-750 ℃ to form a magnetic biochar composite material.
[0010] Further, in step 1, the inorganic acid is hydrochloric acid or sulfuric acid, and after acid washing, the specific surface area of the low-ash carrier is > 200 m 2 / g.
[0011] Further, in step 1, the solid-liquid ratio of the biochar and the inorganic acid solution is 1g: (10-20) mL; Shaking treatment at 80 ℃ for 4-6 h.
[0012] Further, in step 2, the reducing agent and Fe 3+ The molar ratio is 0.3-0.6:1.
[0013] Further, in step 2, the reducing agent is ascorbic acid or sodium sulfite; the iron salt impregnation solution contains a pore-forming agent.
[0014] Further, in step 2, when the low-ash carrier is added to the iron salt impregnation solution, the mass ratio of carbon to iron is controlled to be 5-10:1.
[0015] Further, in step 3, the particle size of the Fe3O4 nanocrystals is 20-50 nm, and the size of the zero-valent iron nanodots is 5-10 nm.
[0016] Further, in step 3, the volume ratio of N2 to H2 is (85-94):(15-6).
[0017] The application also discloses a magnetic biochar composite material prepared by the preparation method, wherein the magnetic biochar composite material is a heterojunction structure of Fe3O4 nanocrystals and zero-valent iron nanodots on the surface of the Fe3O4 nanocrystals, and the saturation magnetization is ≥10 emu / g.
[0018] The application also discloses application of the magnetic biochar composite material in the field of remediation of organic pollutants.
[0019] Compared with the prior art, the application has the following beneficial technical effects: The application provides a preparation method of a magnetic biochar composite material, which removes metal oxide ash such as CaO and MgO in pyrolysis biochar of agricultural waste by inorganic acid shaking treatment, avoids shielding of active sites during subsequent iron loading, and improves iron loading capacity.
[0020] The green rust precursor is generated in a buffer environment with pH 5.5-6.5, the generation of inert impurity phases such as FeO / FeS2 in the traditional iron salt impregnation co-pyrolysis method is avoided, the iron phase agglomeration is reduced, and the dispersion of iron species is improved. The metastable structure of the green rust precursor can be directionally converted into a heterojunction of Fe3O4 nanocrystals and zero-valent iron nanodots in subsequent pyrolysis, and the catalytic activity is enhanced.
[0021] The N2 and H2 combined atmosphere is a weak reduction environment, which can generate Fe3O4 nanocrystals (20-50 nm) and partially reduce them to 5-10 nm zero-valent iron nanodots, effectively inhibiting the agglomeration of iron particles. The generated heterojunction structure makes the saturation magnetization of the material ≥10 emu / g, which is convenient for magnetic separation and recovery, reduces the remediation cost, and avoids secondary pollution.
[0022] Further, the volume ratio of N2 and H2 is designed as (85-94):(15-6), in this "weak reduction atmosphere", Fe3O4 can be generated, and it can be controllably partially reduced to 5-10 nm zero-valent iron nanodots, and effectively inhibit its agglomeration.
[0023] The application provides a magnetic biochar composite material, which is based on an endogenous driving-electron bridging-adsorption catalysis synergy mechanism, and breaks through the design of Fe 0 / Fe3O4 heterojunction loaded biochar material, uses soil endogenous substances (O2 / Fe) as the reaction driving force, combines the electron bridging function of biochar, and establishes an in-situ Fenton technology system: (1) pure endogenous driving: using the inherent O2 and Fe(II) in the soil, avoiding the addition of external oxidants (such as H2O2), and eliminating the risk of secondary pollution; (2) electron conduction revolution: the "conductor-like" network is constructed by the quinone / phenol functional groups of biochar, the electron utilization rate is significantly improved, and the side reaction is reduced; (3) adsorption-catalysis synergy: the high specific surface area enhances the enrichment of pollutants, and the degradation efficiency is significantly improved. The magnetic biochar composite material prepared in the application activates the soil endogenous Fenton-like reaction to repair organic pollutants. Not only the secondary pollution and soil ecological damage caused by the external application of oxidants are avoided, but also the continuous Fe(III) / Fe(II) cycle in the soil Fe(II) / O2 system is promoted, the electron utilization rate of the system is improved, a high yield of hydroxyl radicals (•OH) is continuously generated, and the organic pollutants are efficiently degraded. BRIEF DESCRIPTION OF DRAWINGS
[0024] Figure 1 The specific surface area of the biochar after removing ash in the application is 1,000-1,500 m2 / g. Figure 2 The XRD pattern of the green rust precursor in the application is shown in the figure; Figure 3 The magnetic hysteresis curves of examples 1-2 in the application are shown in the figure; Figure 4aA scanning electron microscope image of the magnetic biochar material prepared for the present application Example 1; Figure 4b A scanning electron microscope image of the magnetic biochar material prepared for the present application Example 2; Figure 4c A scanning electron microscope image of the magnetic biochar material prepared for the present application Example 3; Figure 4d A scanning electron microscope image of the magnetic biochar material prepared for the present application Example 4; Figure 4e A scanning electron microscope image of the magnetic biochar material prepared for the present application Example 5; Figure 4f A scanning electron microscope image of the iron-loaded biochar material prepared for the present application Comparative Example 1; Figure 4g A scanning electron microscope image of the iron-loaded biochar material prepared for the present application Comparative Example 2; Figure 5 Degradation rates of antibiotic and polycyclic aromatic hydrocarbon organic pollutants within 30 days after the magnetic biochar material and iron-loaded biochar material prepared for the present application Examples 1-5 and Comparative Examples 1-2 were applied to the soil, respectively; Figure 6 Toxicity evaluation of degradation products of the magnetic biochar composite material prepared for the present application Example 1 applied to sulfonamide antibiotic contaminated soil; Figure 7 Comparison chart of Fe(II) regeneration rate (h - ¹) and electron utilization rate (%) of the present application compared with prior art; Figure 8 Microbial diversity retention rate chart of the magnetic biochar material prepared for the present application Examples 1-3 after being applied to the soil. DETAILED DESCRIPTION
[0025] In order to make the objectives, technical solutions and advantages of the present application clearer, further detailed description will be made in combination with the accompanying drawings and examples. It should be understood that the specific examples described herein are only used to explain the present application, and are not used to limit the present application, that is, the described examples are only a part of the examples of the present application, but not all examples.
[0026] The detailed description of the examples of the present application provided in the following drawings is not intended to limit the scope of the claimed present application, but only to represent a selected embodiment of the present application. Based on the drawings and examples of the present application, all other examples obtained by those skilled in the art without making creative efforts are within the scope of protection of the present application.
[0027] It is to be understood that the terms "comprising," "including," and other variants thereof, are intended to encompass non-exclusive inclusions, such that processes, elements, methods, articles, or apparatuses that comprise a list of elements are not necessarily limited to those elements, but can include other elements not expressly listed or inherent to such processes, elements, methods, articles, or apparatuses.
[0028] The application discloses a preparation method of a magnetic biochar composite material, comprising the following steps: Step 1, crushing and drying agricultural waste, pyrolyzing under a protective atmosphere at a temperature of 500-700 DEG C to obtain biochar; The biochar is treated with an inorganic acid solution, washed with water until neutral, and dried to obtain a low-ash carrier; Step 2, adding the low-ash carrier into an iron salt impregnation solution, adding a reducing agent solution under a buffer environment with a pH of 5.5-6.5 to generate a green rust type precursor; Step 3, pyrolyzing the green rust type precursor in a mixed atmosphere of N2 and H2 at a temperature of 650-750 DEG C to form the magnetic biochar composite material.
[0029] The features and performances of the application are further described in detail in combination with the following examples.
[0030] Example 1 Step 1, primary pyrolysis and acid washing to remove ash: Crushing and drying agricultural waste (straw and sawdust), pyrolyzing under a nitrogen atmosphere at a temperature of 500 DEG C at a rate of 10 DEG C / min for 2 h to obtain biochar; Treating the biochar with a 1M hydrochloric acid solution at 80 DEG C for 4 h, the solid-liquid ratio of biochar and hydrochloric acid solution being 1g:10mL, washing with water until neutral, and drying to obtain a low-ash carrier; Step 2, in-situ reduction and precipitation: Adding the low-ash carrier obtained in step 1 into a FeCl3 solution, controlling the mass ratio of carbon to iron to be 5:1, adding an ascorbic acid solution drop by drop under a buffer environment with a pH of 5.5, the molar ratio of reducing agent to Fe 3+ being 0.3:1 to generate a green rust type precursor; Step 3, secondary pyrolysis under a weak reduction atmosphere: Pyrolyzing the green rust type precursor in a mixed atmosphere of N2 and H2 with a volume ratio of 94:6 at a temperature of 750 DEG C at a rate of 10 DEG C / min for 1 h to form a magnetic biochar composite material; the magnetic biochar composite material is a heterojunction structure of Fe3O4 nanocrystals and Fe 0 nanopoints on the surface thereof.
[0031] Example 2 Step 1, primary pyrolysis and acid washing to remove ash: Agricultural waste (straw and sawdust) was crushed and dried, then pyrolyzed at 600℃ for 2 h under nitrogen atmosphere at a rate of 10 ℃ / min. The resulting biochar was treated with 1M sulfuric acid solution at 80℃ and shaken for 4 h. After washing with water until neutral, it was dried to obtain a low ash carrier. The solid-liquid ratio of biochar to sulfuric acid solution is 1g:15mL.
[0032] Step 2, in-situ reduction precipitation: The carrier obtained in step 1 was added to FeCl3 solution, and the carbon:iron mass ratio was controlled at 5:1. Ascorbic acid solution was added dropwise under a pH = 5.5 buffer environment to generate a green rust-type precursor and load it. Among them, ascorbic acid and Fe 3+ The molar ratio is 0.4:1.
[0033] Step 3, secondary pyrolysis in a weak reducing atmosphere: The precursor material was pyrolyzed in a mixed atmosphere of N2 and H2 (94:6 volume ratio) at a rate of 10 °C / min to 750 °C for 1 h to form Fe3O4 nanocrystals and Fe on their surface. 0 Heterojunction structure of nanodots.
[0034] Example 3 Step 1: Primary pyrolysis and acid washing for ash removal: Agricultural waste (straw and sawdust) was crushed and dried, then pyrolyzed at 700℃ for 2 h under nitrogen atmosphere at a rate of 10 ℃ / min. The resulting biochar was treated with 1M hydrochloric acid solution at 80℃ for 5 h with shaking, with a solid-liquid ratio of 1:10. After washing with water until neutral, the biochar was dried to obtain a low-ash carrier. The solid-liquid ratio of biochar to hydrochloric acid solution is 1g:20mL.
[0035] Step 2, in-situ reduction precipitation: The carrier obtained in step 1 was added to a mixed solution of FeCl3 and ZnCl2 (volume ratio 1:1), and the mass ratio of carbon:iron:zinc was controlled at 5:1:1. Ascorbic acid solution was added dropwise under a pH = 5.5 buffer environment to generate a porous green rust precursor. Among them, ascorbic acid and Fe 3+ Molar ratio 0.5:1.
[0036] Step 3, secondary pyrolysis in a weak reducing atmosphere: The precursor material was pyrolyzed in a mixed atmosphere of N2 and H2 (94:6 volume ratio) at a rate of 10 °C / min to 650 °C for 1 h to form Fe3O4 nanocrystals and Fe on their surface. 0 Porous heterojunction structure of nanodots.
[0037] Example 4 Step 1: Primary pyrolysis and acid washing for ash removal: Agricultural waste (straw and sawdust) was crushed and dried, then pyrolyzed at 600℃ for 2 h under nitrogen atmosphere at a rate of 10 ℃ / min. The resulting biochar was treated with 1 M sulfuric acid solution at 80℃ for 6 h with shaking, washed with water until neutral, and then dried to obtain a low ash carrier. The solid-liquid ratio of biochar to sulfuric acid solution is 1g:10mL.
[0038] Step 2, in-situ reduction precipitation: The carrier obtained in step 1 was added to FeCl3 solution, and the carbon:iron mass ratio was controlled at 8:1. Sodium sulfite solution was added dropwise under pH = 6 buffer environment to generate a green rust type precursor and load it. Sodium sulfite and Fe 3+ The molar ratio is 0.6:1.
[0039] Step 3, secondary pyrolysis in a weak reducing atmosphere: The precursor material was pyrolyzed in a mixed atmosphere of N2 and H2 (85:15 volume ratio) at a temperature increased to 700℃ for 1 h at a rate of 10℃ / min to form Fe. 0 Heterojunction structure of nanodots.
[0040] Example 5 Step 1: Primary pyrolysis and acid washing for ash removal: Agricultural waste (straw and sawdust) was crushed and dried, then pyrolyzed at 700℃ for 2 h under nitrogen atmosphere at a rate of 10 ℃ / min. The resulting biochar was treated with 1M hydrochloric acid solution at 80℃ for 4 h, washed with water until neutral, and then dried to obtain a low ash carrier. The solid-liquid ratio of biochar to hydrochloric acid solution is 1g:10mL.
[0041] Step 2, in-situ reduction precipitation: The carrier obtained in step 1 was added to FeCl3 solution, and the carbon:iron mass ratio was controlled at 10:1. Ascorbic acid solution was added dropwise under a pH = 6.5 buffer environment to generate a green rust-type precursor and load it. Among them, ascorbic acid and Fe 3+ The molar ratio is 0.3:1.
[0042] Step 3, secondary pyrolysis in a weak reducing atmosphere: The material with the precursor was pyrolyzed in a mixed atmosphere of N2:H2:O2 volume ratio of 94:5:1 at a rate of 10 °C / min to 750 °C for 1 h to form Fe3O4 nanocrystal structure.
[0043] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that iron-loaded biochar was prepared by immersing biomass raw materials in FeCl3 solution for 24 hours and then pyrolyzing them once.
[0044] The specific steps are as follows: Agricultural waste (straw and sawdust) is crushed and dried, then soaked in FeCl3 solution for 24 hours, controlling the carbon:iron mass ratio at 5:1. Ascorbic acid solution, acting as a reducing agent, is added dropwise under a pH = 5.5 buffer environment. The reducing agent reacts with Fe... 3+ With a molar ratio of 0.3, a green rust-type precursor was generated and loaded. The material with the loaded precursor was then pyrolyzed in a mixed atmosphere of N2 and H2 with a volume ratio of 94:6 at 10 °C / min to 750 °C for 1 h to obtain iron-loaded biochar material.
[0045] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that iron-loaded biochar was directly prepared by in-situ precipitation after the first pyrolysis, without secondary pyrolysis.
[0046] The specific steps are as follows: Step 1, pyrolysis and acid washing to remove ash: Agricultural waste (straw and wood chips) is crushed and dried, and pyrolyzed at 500 ℃ for 2 h under nitrogen atmosphere at a rate of 10 ℃ / min. The resulting biochar is treated with 1M inorganic acid (hydrochloric acid or sulfuric acid) solution at 80 ℃ for 4 h with a solid-liquid ratio of 1:10. After washing with water until neutral, it is dried to obtain a low ash carrier. Step 2, In-situ Reduction Precipitation: The carrier obtained in Step 1 is added to FeCl3 solution, controlling the carbon:iron mass ratio at 5:1. Ascorbic acid solution is added dropwise under a pH = 5.5 buffer environment. The reducing agent reacts with Fe... 3+ With a molar ratio of 0.3, the reaction produces a green rust-type precursor, which becomes the final product.
[0047] The magnetic biochar composite material prepared by this invention is a heterojunction structure of Fe3O4 nanocrystals and zero-valent iron nanodots on its surface, with a saturation magnetization ≥10 emu / g.
[0048] Data Analysis: Figure 1 The porous carrier prepared by acid washing of biochar has a specific surface area >200 m². 2 / g indicates that the low ash carrier has abundant pores, which facilitates the loading of iron oxides. It has strong activity and has the potential to be used as an environmental functional material.
[0049] Figure 2 The XRD pattern of the green rust precursor shows that the presence of characteristic peaks at 2θ = 11.2° and 22.6° indicates that Fe... 3+The metastable green rust crystals were directionally transformed into a highly active metastable state, giving them the potential to be used as environmentally functional materials that can be successfully pyrolyzed to produce iron oxides.
[0050] Figure 3 The magnetic hysteresis curves of Examples 1 and 2 illustrate the successful preparation of the magnetic biochar composite material, which has good ferrimagnetism and is very beneficial for the adsorption, diffusion, exchange and magnetic separation of ions.
[0051] Figures 4a to 4g The images shown are scanning electron microscope (SEM) images of the magnetic biochar materials and iron-loaded biochar materials prepared in Examples 1-5 and Comparative Examples 1-2, respectively. It can be seen that they basically retain the original fiber bundle structure (lotus root-like) of the wood chips, and the pore walls are intact. Many particles are attached to the surface and pores, resulting in a rough surface. This indicates the successful preparation of the magnetic biochar composite material and the iron-loaded biochar material. The biochar serves as a supporting substrate for dispersing iron particles or manufacturing iron forms, and can also provide considerable electronic reactivity, mediating reduction or oxidation reactions.
[0052] In Example 3, the pore structure is more developed than that of Example 1 due to the introduction of ZnCl2. The core of this invention lies in constructing "Fe 0 The "Fe3O4 heterojunction" achieves highly efficient Fenton-like catalytic activity. The formation of this core structure depends entirely on the iron salt and subsequent green rust formation and weak reduction pyrolysis steps. The introduction of ZnCl2 does not participate in the chemical composition of this heterojunction. In this invention, ZnCl2 mainly acts as a "pore-forming agent," optimizing the physical structure of the material (increasing specific surface area and porosity), thereby further enhancing its adsorption capacity for pollutants and providing a better dispersion environment for active sites.
[0053] Example 4: Due to excessive reduction during secondary pyrolysis, only zero-valent iron (Fe) was obtained. 0 The presence of (nanodot size 5 nm). In Example 5, due to excessive oxidation during secondary pyrolysis, only Fe3O4 (particle size 30 nm) was present.
[0054] Figure 5The degradation rates of antibiotics and polycyclic aromatic hydrocarbons (PAHs) in soil within 30 days of application of the magnetic biochar materials and iron-loaded biochar materials prepared in Examples 1-5 and Comparative Examples 1-2 of this invention were observed. The degradation rates of antibiotics were 97%, 91%, 94%, 85%, 82%, 73%, and 69%, respectively, while the degradation rates of PAHs were 96%, 93%, 95%, 83%, 84%, 75%, and 64%, respectively. This indicates that the soil endogenous Fenton-like reaction system mediated by the magnetic biochar prepared by the secondary pyrolysis method has a superior remediation effect on organic pollutants, significantly higher than the remediation effect of iron-loaded biochar prepared by the primary pyrolysis method (Comparative Example 1) and the in-situ coprecipitation method (Comparative Example 2).
[0055] Antibiotics inevitably produce degradation intermediates (Px, where x is the mass-to-charge ratio of the degradation intermediates) during the degradation process. Figure 6 To evaluate the toxicity of degradation products of the magnetic biochar material prepared in Example 1 of this invention in soil contaminated with the sulfonamide antibiotic sulfamethoxazole (SMX). The degradation products were determined using triple quadrupole mass spectrometry in positive electrospray ionization mode, and a total of 12 degradation byproducts (P-256, P-257, P-201, P-255, P-269, P-270, P-157, P-175, P-173, P-203, P-123, P-158) were identified. For the traditional Fenton system, most intermediate products of sulfonamide antibiotics still exhibit high developmental toxicity. However, as shown in Figure 6, except for P-256, almost all degradation intermediate products showed lower developmental toxicity than SMX. This indicates that the developmental toxicity of sulfonamide antibiotic-contaminated soil remediated by the magnetic biochar composite material was significantly reduced, and the detoxification effect of the soil Fe(II) / O2 system was superior to that of the traditional Fenton system.
[0056] Figure 7 Compared with existing technologies, the magnetic biochar material prepared in Example 1 of this invention has a higher regeneration rate (h) of ferrous (Fe(II)) ions. - ¹) Comparison of electron utilization rate (%). Through kinetic experiments on Fe(II) regeneration capacity and comparative analysis of electron utilization rate, it was found that the magnetic biochar material prepared in this invention has significant advantages. The Fe(II) regeneration rate is 8 times higher than that of natural iron minerals and 2.6 times higher than that of traditional iron-loaded biochar (Fe / BC) materials; the electron utilization rate is 4.2 times higher than that of natural iron minerals and 0.64 times higher than that of traditional Fe / BC materials. The specific performance index comparison results are shown in Table 1 below.
[0057] Table 1
[0058] Figure 8 The images show the microbial diversity abundance after the magnetic biochar materials prepared in Examples 1-3 of this invention were applied to the soil. Because the application of magnetic biochar materials avoids the killing of microorganisms by strong oxidants, and precisely controls the iron valence state to reduce the inhibition of bacterial communities by dissolved iron ions, while the porous structure of the material provides a habitat for microorganisms, the microbial diversity retention rate is >95%, providing technical support for soil ecological safety restoration.
[0059] This invention uses agricultural waste as biomass raw material and achieves Fe on biochar through a three-step synergistic process: pyrolysis followed by acid washing for ash removal, construction of green rust precursors, and weak reduction phase regulation. 0 The precise construction of Fe3O4 heterojunctions breaks through the limitations of electron transfer efficiency in soil remediation. While avoiding secondary pollution caused by the addition of exogenous oxidants, it achieves efficient degradation of organic pollutants, providing a green, economical, and environmentally friendly soil remediation method.
[0060] (1) The Fe(III) / Fe(II) cycle rate increased by 260% (0.18 vs 0.05 h). - ¹), which solved the bottleneck of electron transfer in traditional systems; (2) High electron utilization rate, while reducing side reactions and doubling the efficiency of reactive oxygen generation; (3) The specific surface area of the acid-washed biochar is >200 m² / g, and the surface is rich in carboxyl hydroxyl groups. These oxygen-containing functional groups can adsorb antibiotics through hydrogen bonds and π-π interactions, and Fe 0 In the Fe3O4 heterostructure, the positively charged Fe3O4 molecules can electrostatically adsorb negatively charged antibiotic molecules, while zero-valent iron provides metal coordination. Furthermore, the hydrophobic organic matter and hydrophilic iron oxides produced during pyrolysis form a unique three-phase distribution system of "soil-organic matter-iron oxide". Hydrophilic antibiotics are adsorbed onto the iron oxide interface, while hydrophobic antibiotics are distributed into the organic matter phase, achieving broad-spectrum inhibition. The Fe3O4 in the heterostructure... 0 As an electron donor, Fe3O4 acts as an electron channel, forming a self-circulating electron transport system, which effectively increases the soil's resistance to antibiotics through a Fenton-like reaction. (4) Without external oxidants, the pollutant degradation rate is >95% and the soil microbial diversity retention rate is >95%.
[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a magnetic biochar composite material, characterized in that, Includes the following steps: Step 1: Crush and dry agricultural waste, then pyrolyze it at 500-700 ℃ under a protective atmosphere to obtain biochar; Biochar was shaken with an inorganic acid solution, washed with water until neutral, and then dried to obtain a low-ash carrier. Step 2: Add the low-ash carrier to the iron salt impregnation solution, and add the reducing agent solution in a buffer environment with a pH of 5.5-6.5 to react and generate a green rust precursor; Step 3: Pyrolyze the green rust-type precursor in a mixed atmosphere of N2 and H2 at 650-750 ℃ to form a magnetic biochar composite material.
2. The method for preparing a magnetic biochar composite material according to claim 1, characterized in that, In step 1, the inorganic acid is hydrochloric acid or sulfuric acid. After acid washing, the specific surface area of the low-ash carrier is >200 m². 2 / g.
3. The method for preparing a magnetic biochar composite material according to claim 1, characterized in that, In step 1, the solid-liquid ratio of biochar to inorganic acid solution is 1 g : (10-20) mL; Shake at 80 ℃ for 4 to 6 hours.
4. The method for preparing a magnetic biochar composite material according to claim 1, characterized in that, In step 2, the reducing agent reacts with Fe 3+ Molar ratio 0.3-0.6:
1.
5. The method for preparing a magnetic biochar composite material according to claim 1, characterized in that, In step 2, the reducing agent is ascorbic acid or sodium sulfite; the iron salt impregnation solution contains a pore-forming agent.
6. The method for preparing a magnetic biochar composite material according to claim 1, characterized in that, In step 2, when the low-ash carrier is added to the iron salt impregnation solution, the carbon:iron mass ratio is controlled to be 5-10:
1.
7. A method for preparing a magnetic biochar composite material according to claim 1, characterized in that, In step 3, the Fe3O4 nanocrystals have a particle size of 20-50 nm, and the zero-valent iron nanodots have a size of 5-10 nm.
8. A method for preparing a magnetic biochar composite material according to claim 1, characterized in that, In step 3, the volume ratio of N2 to H2 is (85~94): (15~6).
9. The magnetic biochar composite material prepared by the preparation method according to any one of claims 1-8, characterized in that, The magnetic biochar composite material is a heterojunction structure of Fe3O4 nanocrystals and zero-valent iron nanodots on its surface, with a saturation magnetization ≥10 emu / g.
10. The application of the magnetic biochar composite material according to claim 9 in the field of remediation of organic pollutants, characterized in that, Applying magnetic biochar composite material to contaminated soil activates O2 to initiate endogenous Fenton-like reactions in the soil, continuously generating hydroxyl radicals and promoting the degradation of organic pollutants.